2000
DOI: 10.1590/s0034-71082000000300017
|View full text |Cite
|
Sign up to set email alerts
|

Description and prevalence of Thynnascaris sp. larvae Dollfus, 1933 (Nematoda: Anisakidae) in Plagioscion squamosissimus Heckel, 1840 from Volta Grande Reservoir, State of Minas Gerais, Brazil

Abstract: The present work studied helminth parasites of freshwater "corvina" Plagioscion squamosissimus from Volta Grande Reservoir, MG, Brazil. Sixty eight fishes with averages of 25.2 cm length and 180.9 g weight were collected with net, bimonthly from December 1995 thru December 1996. Parasites were carefully removed from their cysts that were present in the intestinal mesentery. Specimens were fixed in AFA 65 degrees C and preserved in alcohol 70% with 5% of glicerine. In camera lucida 21 nematodes were drawned aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…In this assay, neutrophill migration was more pronounced by saline and thioglycollate injections which were also corroborated by the findings of Do Vale et al (2002). Finally, these results might explain the migration of cells involved in the inflammatory response caused by parasites in native fish (Martins et al, 2000(Martins et al, , 2001b.…”
Section: Discussionmentioning
confidence: 99%
“…In this assay, neutrophill migration was more pronounced by saline and thioglycollate injections which were also corroborated by the findings of Do Vale et al (2002). Finally, these results might explain the migration of cells involved in the inflammatory response caused by parasites in native fish (Martins et al, 2000(Martins et al, , 2001b.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported 23 parasitic species in the South American silver croaker, including one cestode (WOODLAND, 1935), two digenetic (THATCHER, 1979;KOHN et al, 1995), 12 monogeneans (KRITSKY & THATCHER, 1984;MARTINS et al, 2000a;KRITSKY & BOEGER, 2002;BOEGER & KRITSKY, 2009), two acanthocephalans (THATCHER, 1980MELO et al, 2015), four nematodes (MORAVEC et al, 1993;MARTINS et al, 2000b;TAVARES et al, 2007) and two copepod crustaceans (AMADO & ROCHA, 1996;THATCHER, 1998). Most of these studies were conducted in the Amazon and Paraná basins.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, there are many records of helminth parasites in this host, including anisakid species (MARTINS et al, 2000;TAVARES et al, 2007;EIRAS et al, 2010;DIAS et al, 2011;MELO et al, 2014;RODRIGUES et al, 2015).…”
Section: Introductionmentioning
confidence: 99%